The Prediction of Metastases of Lateral Cervical Lymph Node in Medullary Thyroid Carcinoma - Zhou, Tian-Han; Zhao, Ling-Qian; Zhang, Yu; Wu, Fan; Lu, Kai-Ning; Mao, Lin-Lin; Jiang, Ke-Cheng; Luo, Ding-Cun (Frontiers in Endocrinology, 2021)
Abstract Purpose: Development and validation of a nomogram for prediction of lateral lymph node metastasis (LLNM) in medullary thyroid carcinoma (MTC). Methods: We retrospectively reviewed the clinical features of patients with MTC in the surveillance, epidemiology, and end results (SEER) database between 2010 and 2017 and in our Department of Surgical Oncology, Hangzhou First People’s Hospital between 2009 and 2019. The log‐rank test was used to compare the difference in the Kaplan‐Meier (K‐M) curves in recurrence and survival. The nomogram was developed to predict the risk of LLNM in MTC patients. The prediction efficiency of the predictive model was assessed by area under the curve (AUC) and concordance index (C-index) as well as calibration curves. Decision Curve Analysis (DCA) was performed to determine the clinic value of the predictive model. Result: A total of 714 patients in the SEER database and 35 patients in our department were enrolled in our study. Patients with LLNM had worse recurrence rate and cancer-specific survival (CSS) compared with patients without LLNM. Five clinical Characteristics including sex, tumour size, multifocality, extrathyroidal extension, and distant metastasis were identified to be associated with LLNM in MTC patients, which were used to develop a nomogram. Our prediction model had satisfied discrimination with a C-index of 0.825, supported by both training set and internal testing set with a C-index of 0.825, and 0.816, respectively. A DCA was further made to evaluate the clinical utility of this nomogram for predicting LLNM. Conclusions: Male sex, tumour size>38mm, multifocality, extrathyroidal extension, and distant metastasis in MTC patients were significant risk factors for predicting LLNM. Our results may thus serve as a predictor for LLNM in MTC and may perhaps also be referenced in preoperative discussions with patients regarding surgical methods.